LESIONS OF THE LATERAL HYPOTHALAMUS IMPAIR THE PRESSOR-RESPONSE TO CLONIDINE INJECTED INTO THE MEDIAL SEPTAL AREA OF CONSCIOUS RATS - Haibara, A. S.; Camargo, LAA; Saad, W. A.; Renzi, Antonio [UNESP]; Deluca, L. A.; Menani, José Vanderlei [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1992)
The central injection of clonidine (an alpha-2-adrenoceptor agonist) in conscious normotensive rats produces hypertensive responses and bradycardia. The present study was performed to investigate the effect of electrolytic lesions of the lateral hypothalamus (LH) on the pressor and bradycardic responses induced by clonidine injected into the medial septal area (MSA) in conscious and unrestrained rats. Male Holtzman rats weighing 250-300 g were used. Mean arterial pressure and heart rate were recorded in sham- or bilateral LH-lesioned rats with a cerebral stainless steel cannula implanted into the MSA. The injection of clonidine (40 nmol/mu-l) into the MSA of sham rats (N = 8) produced a pressor response (36 +/- 7 mmHg, P<0.05) and bradycardia (-70 +/- 13 bpm, P<0.05) compared to saline. Fourteen days after LH-lesion (N = 9) the pressor response was reduced (9 +/- 10 mmHg, P<0.05) but no change was observed in the bradycardia (-107 +/- 24 bpm). These results show that LH is an important area involved in the pressor response to clonidine injected into the MSA of rats.
Keywords: ARTERIAL PRESSURE; HYPOTHALAMUS; BRADYCARDIA; ADRENERGIC RECEPTORS; SEPTAL AREA; CLONIDINE; MEDIAL SEPTAL AREA; LATERAL HYPOTHALAMUS